Fate of Pediatric Transport Medicine Abstracts 2011 to 2020: What Predicts Publication Success? - Rozenfeld, Ranna A.; Noje, Corina (Air medical journal, 2024)
Pediatric-neonatal transport research projects are presented at the American Academy of Pediatrics (AAP) Section on Transport Medicine (SOTM) scientific abstract program annually. Journal publication increases the impact of these projects. Our objectives were to determine the publication rate of transport abstracts and to identify factors predictive of publication success. We reviewed all AAP SOTM abstracts accepted for presentation from 2011 to 2020 and assessed presentation format (oral/platform vs. poster), authors’ professional degree (physician vs. nonphysician), and first author's trainee status. We searched PubMed, Ovid, and ResearchGate for publications by abstract title and authors and then compared published versus unpublished abstracts. Categorical variables were expressed as proportions and compared using the chi-square test or the Fisher exact test, whereas continuous variables were summarized using medians and interquartile ranges (IQRs) and compared using the Student t-test or the Kruskal-Wallis test as appropriate. A linear probability model was performed. Of 194 presented abstracts, 67 (34.5%) were published. The publication rate was significantly higher for oral/platform versus poster abstracts (P < .01), if the abstract was an oral/platform (probability increase by 19.5%, P < .01), and if the first author was a trainee (probability increase by 25.6%, p < 0.05). The constant was estimated as 24.9% probability of publication. Hence, if the first author was a physician, a trainee, and had an oral/platform presentation, there was an 85.8% chance of being published. The median (IQR) time to publication was 2 years (IQR: 2-4 years), with articles published the longest having the most citations. Articles were published in 27 different journals, with nearly half (33/67, 49.3%) being published in 3 journals. AAP SOTM abstracts have a 34.5% publication rate over the past 10 years, which is consistent with other medical specialties. Oral abstracts, physician first authors, and trainee first authors had a significantly higher success rate. Special emphasis should be placed nationally on supporting nonphysician transport professionals to publish their work.